Review of the new, revised and modernized digital edition of the book Musical Education Through the Keyboard volume 1 -Musicalization, by Maria de Lourdes Junqueira Gonçalves and Cacilda Borges Barbosa. Editors: Tiago Batistone and Ingrid Barancoski.: Student's book and Teacher's Manual (Revista da Tulha, 2020)
Review of a new edition of the first volume of the work Musical Education through the Keyboard of Maria de Lourdes Junqueira Gonçalves and Cacilda Borges Barbosa (student book - 9th edition and teacher manual - 3rd. edition). This revised and modernized edition, the first in a digital format, is the result of a research work by Tiago Batistone with a PIBIC Scientific Initiation scholarship under the supervision and coordination of Profa. Dr. Ingrid Barancoski, professor at the Federal University of the State of Rio de Janeiro (UNIRIO).